Composite Synthetic Scaffolds for Tissue Engineering and Regenerative Medicine - Sultana, Naznin; Hassan, Mohd Izzat; Lim, Mim Mim (SpringerBriefs in Materials, 2015)
This book addresses important biomaterials which are commonly used to fabricate scaffolds and it describes two major protocols employed in scaffold fabrication. Tissue engineering or regenerative medicine aims at restoring ex-novo tissues and organs whose functionality has been compromised as a consequence of diseases or traumatic events. The innovative concept underlying tissue engineering is the use of autologous cells, obtained from a biopsy of the patient. Cells are seeded on a porous scaffold which has the role of supporting and guiding cells towards the development of tissue-like structures as well as providing a platform for the delivery under controlled condition of growth factor release, etc. The successful manufacture of scaffolds for tissue engineering applications is crucial. In this book, these biomaterials are discussed. The book also covers illustrated examples, structure and properties of scaffolds, cellular interactions and drug delivery.